Analyzing Overdispersed Antenatal Care Visits of Pregnant Women in Bangladesh: Negative Binomial Regression Model (Dhaka University Journal of Science, 2017)
The main aim of this paper is to find out the potential determinants of antenatal care visits of women in Bangladesh during their pregnancy. The data set was extracted from Bangladesh Demographic and Health Survey, 2014 and overdispersion is found to be present in the data set. To take the overdispersion into account, negative binomial regression model has been used. A number of socioeconomic and demographic variables were observed to have significant impact on the antenatal care visit. Results are explained using incidence rate ratio.Dhaka Univ. J. Sci. 65(2): 133-137, 2017 (July)